The Effect of PBL Integrated with Renewable Energy Issues on High School Students' Scientific Literacy in Energy Sources - Ahmad Khairul Pajri; Rosane Medriati; Andik Purwanto (Universitas Lambung Mangkurat, 2026)
Low scientific literacy and the absence of contextual physics learning remain persistent challenges in science education. This study aims to investigate the impact of Problem-Based Learning (PBL) integrated with renewable energy issues on high school students' scientific literacy in energy sources. A quasi-experimental pretest-posttest control group design was employed, involving 68 tenth-grade students at SMA Negeri 8 Bengkulu City selected through purposive sampling. Data were gathered using context-based essay tests aligned with the PISA 2022 framework. Results from the Mann-Whitney test (p = 0.002 < 0.05) confirmed that PBL incorporating renewable energy issues significantly impacted scientific literacy. The experimental group outperformed the control group with a higher average posttest score (93.06 vs. 81.97) and a moderate effect size (r = 0.371). These findings demonstrate that integrating real-world energy contexts into PBL effectively improves students' scientific literacy achievements. Therefore, this model is recommended as a meaningful contextual strategy, in which teachers can incorporate local issues—such as the potential of Micro-hydro Power Plants (PLTMH) to concretize renewable energy concepts.